2
$\begingroup$

Given the expression

$$\frac{(2+{\sqrt 3})^{2k-1}+(2-{\sqrt 3})^{2k-1}}{2}-1$$

prove that for positive integer k, this expression results in a perfect square.

My attempt: I tried to prove this by induction. The base step is easy to check, assuming the expression is true for $k=n$, I have no idea how to proceed with $k=n+1$. Any help would be appreciated.

$\endgroup$
3
$\begingroup$

Note $$I=\frac{(2+{\sqrt 3})^{2k-1}+(2-{\sqrt 3})^{2k-1}}{2}-1 =\left(\frac{(2+{\sqrt 3})^{k}}{\sqrt3+1}- \frac{(2-{\sqrt 3})^{k}}{\sqrt3-1} \right)^2 $$

So, it suffices to prove

\begin{align} & S_k = \frac{(2+{\sqrt 3})^{k}}{\sqrt3+1}- \frac{(2-{\sqrt 3})^{k}}{\sqrt3-1}= n\\ & C_k = \frac{(2+{\sqrt 3})^{k}}{\sqrt3+1}+ \frac{(2-{\sqrt 3})^{k}}{\sqrt3-1}=m\sqrt3 \end{align}

where $m$ and $n$ are integers. Then, by induction with $S_1=1$ and $C_1=\sqrt3$

\begin{align} &S_{k+1} = 2S_k +\sqrt3C_k = 2n+ 3m\\ &C_{k+1} = 2C_k +\sqrt3S_k = (2m+n)\sqrt3 \end{align}

Thus, $I$ is a perfect square.

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

Notice that $$(2+\sqrt{3})^{2k-1}=a+b\sqrt{3}\tag{1}$$ for suitable integers $a,b$ (for any $x,y \in \mathbb{Z}[\sqrt{3}]$ we have $xy \in \mathbb{Z}[\sqrt{3}]$, i.e. it is closed under multiplication). Similarly for conjugate, we get $$(2-\sqrt{3})^{2k-1}=a-b\sqrt{3}\tag{2}.$$ Adding the two, we can verify that $a-1$ is the number we need to show to be a perfect square.

Applying binomial theorem on $(2+\sqrt{3})^{2k-1}$, we get $$ a=\sum_{i=0}^{k-1}\binom{2k-1}{2i}2^{2k-2i-1}3^i. $$ Thus $a \equiv 0 \bmod 2$, and so $a-1$ is odd. Similarly, $a \equiv 2^{2k-1} \equiv 2 \bmod 3$, and so $3 \mid a+1$.

Finally, multiplying out $(1)$ and $(2)$, we see $1=a^2-3b^2$. But then $$ (a-1)\left(\frac{a+1}{3}\right)=b^2 \tag{3}, $$ and since $a-1$ is odd, $a-1$ and $a+1$ are coprime. Then $(3)$ implies $a-1$ is a perfect square.

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

$$\dfrac{(2+{\sqrt 3})^{2k-1}+(2-{\sqrt 3})^{2k-1}}{2}-1$$ $$=\dfrac{(2+{\sqrt 3})^{2k-1}+\left(\frac{1}{2+{\sqrt 3}}\right)^{2k-1}-2}{2}$$ $$=\dfrac{\left((2+{\sqrt 3})^{2k-1}\right)^2-2(2+{\sqrt 3})^{2k-1}+1}{2(2+{\sqrt 3})^{2k-1}}$$ $$=\dfrac{\left((2+{\sqrt 3})^{2k-1}-1\right)^2}{2(2+{\sqrt 3})^{2k-1}}$$ $$=\left(\dfrac{(2+{\sqrt 3})^{2k-1}-1}{\sqrt2(2+{\sqrt 3})^{k-\frac12}}\right)^2$$ $$=\left(\dfrac{(2+{\sqrt 3})^{2k-1}-1}{\frac{2(2+{\sqrt 3})^{k}}{\large \sqrt2\cdot \sqrt{2+\sqrt3}}}\right)^2$$ $$=\left(\dfrac{(\sqrt{4+2\sqrt3})((2+{\sqrt 3})^{2k-1}-1)}{2(2+{\sqrt 3})^{k}}\right)^2$$ $$=\left(\dfrac{(\sqrt3+1)\left((2+{\sqrt 3})^{k-1}-(2-\sqrt3)^k\right)}{2}\right)^2$$ Above is always a square number.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.